Recent UAS aerodynamics testing activities at WSU-NIAR - Kelly, Kevin W. (Kansas State University, 2013)
Since 2009, the Walter H. Beech Wind Tunnel (WBWT) at Wichita State University’s National Institute for Aviation Research has provided significant aerodynamic testing services in support of eleven unmanned aerial systems (UAS), aerial target, missile, and bomb development programs. The goal of the presentation is to educate the Kansas UAS industry on the capabilities and value of wind tunnel testing at the WBWT.
Keywords: Wichita State University; National Institute for Aviation Research; Unmanned air vehicles; Aerodynamics; Wind tunnel testing; Walter H. Beech Wind Tunnel